INTELLECTUAL CAPITAL: INFORMATION DISCLOSURE PRACTICES BY PORTUGUESE COMPANIES - Cruz, Juliana Catarina Santos (2013)
As time went on, people acknowledged that the accounting value of an organization differs from its market value and that this gap stems, in part, from the difficulty of recognition and measurement of intangible assets. Intellectual capital encompasses also the intangible assets that are not recognized due to the fact that they do not satisfy the conditions of the applied accounting standards. Yet, they create value. Therefore, its disclosure is relevant. The main purpose of this study is to analyze the practices of intellectual capital information disclosure of the organizations in the selected sample and its determinants. We highlight the role of theory in explaining the voluntary disclosure of this specific type of information. We used content analysis to collect the data about intellectual capital and to develop the descriptive and statistical analysis. We tested the relationship between size, industry, age and debt ratio of each organization and the level of disclosure about intellectual capital and its components. We applied logistic regression to validate the hypotheses. Based on the sample composed by fourteen listed companies in Euronext Lisbon in 2009, we noticed that the sign of the relationship between the explanatory variables and those which have been explained is, generally, positive. However, we found out a small number of statistically significant relationships. The results of content analysis show that the organizations studied emphasize intellectual capital information.